Alternative Cultural Institutions in Germany: Questioning Economic Perspectives on Spaces of Creativity - Mager, Christoph (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
In 2007 the German Bundestag issued an extensive parliamentary report on “Culture in Germany” that spurred broad debates about the role of cultural institutions in urban and regional planning. Subsequently, these infrastructures gained particular importance in discussions on the cultural and creative industries as nodes for professional activities and marketplaces for cultural goods. By analyzing the material and discursive trajectories of alternative cultural and community centres in Germany the paper argues that economic perspectives on spaces of creativity obscure important dimensions of creative practices. Firstly, conceptions of creativity as a defining feature of occupations and economic sectors imply that creative pursuits are ultimately determined by patterns of supply and demand. Mundane activities on a day-to-day basis however show that alternative creativities are frequently driven by voluntary engagements, personal desires and affection towards people and ideas. Secondly, as studies on the creative industries offer rather current diagnoses of cultural infrastructures the historical dimension of political discussions is often missing from theses analyses. Established since the 1960s, alternative cultural institutions are conceptualized as sustainable meeting places that offer spaces for communication, self-determination and free play. Finally, creative industry thinking emphasizes specific geographical contexts for creative production. The overriding observation is one of urban agglomeration and spatial clustering. The mapping of alternative cultural infrastructures reveals a more complex and nuanced geography of non-profit creativity that encompasses material spaces in suburban and more rural areas. Cultural and community centres offer an important and sometimes occasional anchor point for creativity in these peripheries lacking publicly funded and privately financed cultural infrastructures.